2004
DOI: 10.1016/j.ejcts.2004.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Vasomotor dysfunction after cardiac surgery

Abstract: Cardiopulmonary bypass and cardioplegic arrest, which allow for support of the circulation and stabilization of the heart during cardiac procedures, are still used for the vast majority of cardiac operations worldwide. However, in addition to a well-recognized systemic inflammatory response, cardiopulmonary bypass and cardioplegic arrest elicit complex, multifactorial vasomotor disturbances that vary according to the affected organ bed, with reduced vascular resistances in the skeletal muscle and peripheral ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
107
1
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(120 citation statements)
references
References 145 publications
(180 reference statements)
9
107
1
3
Order By: Relevance
“…Dysfunction of the coronary microcirculation due to diabetes and CP/CPB may result in detrimental effects in myocardial perfusion and function. 2,18,20,21 In conclusion, CP/CPB was associated with alterations in myocardial expression and activation of MAPKs as well as vasomotor dysfunction of coronary arterioles in patients with CABG. Uncontrolled diabetes or diabetes combined with CP/ CPB further altered expression and activation of MAPKs, such as p38-MAPK, ERK1/2, JNK, and MKP-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysfunction of the coronary microcirculation due to diabetes and CP/CPB may result in detrimental effects in myocardial perfusion and function. 2,18,20,21 In conclusion, CP/CPB was associated with alterations in myocardial expression and activation of MAPKs as well as vasomotor dysfunction of coronary arterioles in patients with CABG. Uncontrolled diabetes or diabetes combined with CP/ CPB further altered expression and activation of MAPKs, such as p38-MAPK, ERK1/2, JNK, and MKP-1.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Recent studies in our laboratory demonstrated that PKC-alpha and PKC-beta are upregulated and activated in the human diabetic (type 2) myocardium in the setting of CP/CPB. [15][16][17][18][19][20][21] Whether diabetes, particularly if combining with CP/CPB and cardiac surgery, further affects MAPKs signaling in the human myocardium has not been investigated.…”
mentioning
confidence: 99%
“…Surgical procedures such as cardiopulmonary bypass and organ transplantation provoke ischemia/reperfusion (IR) injury leading to an intense systemic inflammatory response and multiple organs failure that have been associated with high mortality rate [1][2][3]. The genesis of IR-induced deleterious effects has been linked to a massive reactive oxygen species (ROS) production by vascular endothelium and leukocytes [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Ruel et al demonstrated that altered release of NO after cardiac surgery with CPB may lead to reduced peripheral and pulmonary resistance, and abnormal vascular permeability. Furthermore, these abnormalities may lead to organ dysfunction, such as organ edema, impaired regulation of myocardial perfusion and can contribute to myocardial and endothelial dysfunction [28]. Thus, this observed vasomotor dysfunction might be induced by the eNOS G894T polymorphism and/or CPB leading to an increased susceptibility to cleavage of the eNOS protein of the T genotypes.…”
Section: Discussionmentioning
confidence: 99%